Extracellular electron transfer by the cultured coral photosymbiont Symbiodinium microadriaticum - Loris Marcel; James T. Simon; Joshua M. Lawrence; Svetlana Menkin; Adrian C. Barbrook; R. Ellen R. Nisbet; Christopher J. Howe; Jenny Z. Zhang (Photosynthesis Research, 2026)
Photosynthetic microorganisms may show extracellular electron transfer (EET), in which some of the electrons generated by photosynthesis or respiration are lost from the cell. Most studies have focussed on cyanobacteria, with very few on eukaryotic algae. Here we demonstrate EET from the eukaryotic dinoflagellate alga Symbiodinium microadriaticum , a species that can form symbiosis with corals and other Cnidaria. We show that the EET involves diffusible electroactive species, which may represent a previously unsuspected route for communication between symbionts and hosts. We show that EET can be used to study photosynthetic and respiratory functions in the dinoflagellate. We also show that it can provide information on the effects of environmental stresses including changes in temperature (linked to coral bleaching), pH and light intensity. The electrochemical platform outlined in this study offers a novel tool for studying dinoflagellate physiology, the coral-dinoflagellate symbiosis, and the molecular mechanisms of bleaching.